2011
DOI: 10.1007/s12594-011-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact on groundwater of Maheshwaram Watershed, Ranga Reddy district, Andhra Pradesh

Abstract: Maheshwaram watershed is situated in Ranga Reddy district of at a distance of about 30 km south of Hyderabad. The watershed has an area of 53 km 2 and has hard rock aquifers with semi-arid climate. The study area has been expanding at a fast pace and now has the distinction of being one of the fastest growing urban centers, facing the problem of groundwater depletion and quality deterioration due to the absence of perennial source of surface water and also due to over exploitation. Human activities involving i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 4 publications
0
13
0
1
Order By: Relevance
“…Subsequently, most of the industries in developing countries like Bangladesh directly discharge tons of untreated or improperly treated effluents containing algal nutrients, non-biodegradable organics, heavy metals, and other toxicants into nearby lagoon, rivers, and streams [55,56]. Such contamination adversely affects the abiotic compartment such as sediments, aquatic ecosystems (fluctuations within temperature, salinity, pH, dissolved oxygen, and the biological oxygen demand levels), bioaccumulation, or biomagnifications in aquatic lives, and increased nutrient loads of the receiving water bodies [51,52,57,58]. The microbial load was nil in case of E. coli, Salmonella spp., Shigella spp., and Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, most of the industries in developing countries like Bangladesh directly discharge tons of untreated or improperly treated effluents containing algal nutrients, non-biodegradable organics, heavy metals, and other toxicants into nearby lagoon, rivers, and streams [55,56]. Such contamination adversely affects the abiotic compartment such as sediments, aquatic ecosystems (fluctuations within temperature, salinity, pH, dissolved oxygen, and the biological oxygen demand levels), bioaccumulation, or biomagnifications in aquatic lives, and increased nutrient loads of the receiving water bodies [51,52,57,58]. The microbial load was nil in case of E. coli, Salmonella spp., Shigella spp., and Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the study performed by Purushotham et al (2011) showed that about 28% of total hardness in the study site exceeded the desirable limits at 600 mg L -1 . Naturally, the water hardness is due to the presence of alkaline earths such as calcium (Ca) and magnesium (Mg).…”
Section: Metalsmentioning
confidence: 81%
“…The salts present in the groundwater influence the soil structure, permeability and aeration, which indirectly affect the plant growth. Study conducted by Purushotham et al (2011) showed high sodium conductivity (>1500 μs cm -1 ) around 17.5% of the groundwater samples and this probably due to high salinity in groundwater. Sodium concentration in irrigation water replaces calcium by the process of Base Exchange, therefore reduces soil permeability.…”
Section: Organic Matter/inorganic Mattermentioning
confidence: 94%
“…A salinização nas terras irrigadas é a principal causa de perda de produção, e tem impactos ambientais adversos. Condições salinas limitam severamente a escolha das culturas e afetam negativamente a germinação e o rendimento, reduzindo a atividade osmótica das plantas e interferindo na absorção de água e nutrientes do solo (PURUSHOTHAM et al 2011).…”
Section: Avaliação Da Qualidade Da áGua Subterrânea Para Uso Na Agricunclassified